Research on the rheological properties of bitumen modified with waste photopolymer - Kok, Baha Vural; Irhan, Bekir; Yilmaz, Mehmet; Yalcin, Erkut (Elsevier Sci Ltd, 2022)
Recently, the use of waste materials in bitumen modification has become very important in terms of protecting natural resources, reducing environmental pollution, and increasing efficiency. Today, thousands of tons of photopolymer plates are produced every year for printing works and they become waste directly after use. Moreover, the products produced by 3D printers using photopolymer materials have the potential to become waste over time. Photopolymer (PhP) seems to be a suitable material for bitumen modification due to the precious polymers it contains. In this study, PhP obtained from waste solid sheet plates was ground and added to bitumen at 4 different rates. The performance of PhP modified bitumen was compared to pure bitumen and styrene-butadienestyrene (SBS) modification. Softening point, penetration, viscosity, dynamic shear rheometer (DSR), multi-stress creep recovery (MSCR) bending beam rheometer (BBR), storage stability tests and Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis were conducted. In conclusion, it was determined that PhP offered superior properties compared to pure binder with its high softening point, viscosity, complex modulus and low phase angle values. The 9 % PhP modification was similar in many respects to the 5 % SBS modification. Addition of 7 % PhP to pure bitumen (PG 58) made the binder capable of handling extremely heavy traffic conditions at 64 degrees C. The PhP modification behaved more flexibly than SBS at low temperatures and was somewhat more stable in terms of storage. There was physical changes in the structure even though there was no chemical reaction in the binder with the use of PhP and SBS.
Keywords: Waste photopolymer; SBS; Bitumen; Modification; Rheological properties